The Effect of Kyolic Aged Garlic Extract on Gut Microbiota, Inflammation, and Cardiovascular Markers in Hypertensives: The GarGIC Trial - Ried, Karin; Travica, Nikolaj; Sali, Avni (Frontiers in Nutrition, 2018)
Background: Previous research suggests Kyolic-aged-garlic-extract to be effective in reducing blood pressure in a large proportion of hypertensive patients similar to first-line standard antihypertensive medication. High blood pressure has been linked to gut dysbiosis, with a significant decrease in microbial richness and diversity in hypertensives compared to normotensives. Furthermore, gut dysbiosis has been associated with increased inflammatory status and risk of cardiovascular events. Objective: To assess the effect of Kyolic aged GARlic extract on Gut microbiota, Inflammation, and Cardiovascular markers, assessed by blood pressure, pulse wave velocity and arterial stiffness. Methods: A total of 49 participants with uncontrolled hypertension completed a double-blind randomised placebo-controlled trial of 12-weeks, investigating the effect of daily intake of aged-garlic-extract (1.2g containing 1.2mg S-allylcysteine) or placebo on blood-pressure, pulse-wave-velocity and arterial-stiffness, inflammatory markers, and gut microbiota. Results: Mean-blood-pressure was significantly reduced by 10±3.6 mmHg systolic and 5.4±2.3 mmHg diastolic compared to placebo. Vitamin B12 status played a role in responsiveness to garlic on blood pressure in 17% of patients. Garlic significantly lowered central blood pressure, pulse pressure and arterial stiffness (p<0.05). Trends observed in inflammatory markers TNF-α and IL-6 need to be confirmed in larger trials. Furthermore, aged-garlic-extract improved gut microbiota, evident by higher microbial richness and diversity with a marked increase in Lactobacillus and Clostridia species after 3 months of supplementation. Conclusions: Kyolic-aged-garlic-extract is effective in reducing blood-pressure in patients with uncontrolled hypertension, and has the potential to improve arterial stiffness, inflammation, and gut microbial profile. Aged-garlic-extract is highly tolerable with a high safety profile as a stand-alone or adjunctive anti-hypertensive treatment, with multiple benefits for cardiovascular health.